2007
DOI: 10.1002/art.23054
|View full text |Cite
|
Sign up to set email alerts
|

Hyperexpression of cyclooxygenase 2 in the lupus immune system and effect of cyclooxygenase 2 inhibitor diet therapy in a murine model of systemic lupus erythematosus

Abstract: Objective. To investigate the role of cyclooxygenase 2 (COX-2) in the functioning of different cell types involved in the lupus autoimmune response, and to examine the therapeutic effect of COX-2 inhibitors in mice prone to spontaneously develop systemic lupus erythematosus (SLE).Methods. Lupus-prone (SWR ؋ NZB)F 1 mice were fed with a diet containing different doses of the COX-2-specific inhibitor celecoxib or the nonspecific inhibitor aspirin, or a combination of both, and the effects of the therapy on autoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 46 publications
2
32
0
1
Order By: Relevance
“…Although it provides further support for the contention of Phipps and colleagues (8,9) that COX-2 inhibitors are contraindicated after vaccine administration, it also raises the possibility that inhibitors of the COX-2 pathway could profit patients with B cell autoimmunity. In support of the latter, intermittent treatment of mice prone to systemic lupus erythematosus with COX-2 inhibitor resulted in reduced IgG autoantibody titers and improved survival (98). Interference with the COX-2/mPGES-1/EP2 pathway might be particularly important for patients with Sjögren's syndrome, a salivary gland disorder characterized by salivationimpairing IgG autoantibodies (99) and a high predisposition to lymphoma (100,101).…”
Section: Discussionmentioning
confidence: 99%
“…Although it provides further support for the contention of Phipps and colleagues (8,9) that COX-2 inhibitors are contraindicated after vaccine administration, it also raises the possibility that inhibitors of the COX-2 pathway could profit patients with B cell autoimmunity. In support of the latter, intermittent treatment of mice prone to systemic lupus erythematosus with COX-2 inhibitor resulted in reduced IgG autoantibody titers and improved survival (98). Interference with the COX-2/mPGES-1/EP2 pathway might be particularly important for patients with Sjögren's syndrome, a salivary gland disorder characterized by salivationimpairing IgG autoantibodies (99) and a high predisposition to lymphoma (100,101).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, ASA and celecoxib exhibited therapeutic efficacy against the autoimmune murine model of systemic lupus erythematosus. The intermittent pulse therapy with ASA and celecoxib caused a significant inhibition of autoantibodies production and T cell response through the COX-II inhibitory mechanism [137].…”
Section: Clinical Prospects Of Asa With Respect To the Immunopathologmentioning
confidence: 99%
“…This may be due to relatively shorter period of time of simvastatin treatment. In another study, Shurin et al found methotrexate are not able to inhibit maturation of DCs [25] , and celexoib is able to promote apoptosis of DCs [26] , suggesting the reduction of hyperfunction of DCs may be unlikely to be related to use of methotrexate or celexoib.…”
Section: Discussionmentioning
confidence: 97%